Evaluation of maize hybrids under three densities in the agricultural frontier in Maranhão State, Brazil - Lima, Carlos Ferreira de; Arnhold, Emmanuel; de Araújo, Breno Luciano; Ferreira de Oliveira, Gustavo Hugo; de Oliveira Júnior, Edvaldo Aguiar (Federal University of Piauí, 2012)
The aim of this study was to evaluate the agronomic performance of corn hybrids in three densities. The experimental design was randomized block in factorial 2x3 with four replications. No interaction between cultivars and density for any of the characters. Significant differences among hybrids, except for the number of rows of grain. The hybrid 2B707 showed greater height, ear length, number of kernels per row, ear weight and grain yield. The 2B710 hybrid overcomes 2B707 in ear diameter and grain weight. It was found that increasing the density a significant decrease in spike length, number of kernels per row and average ear weight. Also there was a decrease, but not significantly, with increasing density, the number of rows and weight of 100 grains. The ideal population was 55,000 plants where the yield was higher.